Various views on the organizational values of Slovenian managers and enterpreneurs - Boštjančič, Eva (Psihološka obzorja (Ljubljana), 2009)
Processes take place at various levels within an organization. Values thus form a part of organizational culture. They are usually developmed artificially, whereby employees with a higher level of education more often assume internal values and those with lower levels of education assume external values. This study focuses on establishing differences in identifying these values among managers and enterpreneurs. As part of the GLOBE project, the organizational values scale developed by Robert House and collegues (1997) was used. Fifty-nine leaders and 565 of their employees were included in the study. The results whow that the two groups studies were most similar when assessing the values of consumer satisfaction and impacts on the organization's long-term competitiveness and there was no statistically significant difference between enterpreneurs and managers in the assessments of values.
Keywords: management; vrednote; organizacije; GLOBE; Slovenia; Slovenija; psihologija osebnosti